Comparative analysis of the effectiveness and efficiency of three waterproofing systems - dos Santos Kimick, Renata; Gazolla, Micheli; Moura da Silva Junior, Renato; Brandão Capraro, Ana Paula; Moreira, Kirke (Revista ALCONPAT, 2021)
The objective of this study was to comparatively analyze waterproofing systems used in Brazil. The evaluated products were: asphalt emulsion, acrylic resin and thermoplastic resin. In order to evaluate the effectiveness of the systems the tests measured the tightness and the absorption by immersion and capillarity, the last one was also analyzed by thermographic images. For the systems efficiency analysis an accelerated aging pattern was adopted, which consisted of alternating the samples in wet and dry cycles. The results indicate a good performance for the studied systems, in comparison to the non-impermeable series, it presented lower absorbance (approximately 300%). The accelerated aging test indicated, after 140 days of age, a reduction in the performance of the waterproofed serie.